Safety of water supply system operation in conditions of providing fire protection requirements - Zimoch, Izabela; Waloszyński, Marian; Gibki, Tomasz (Instal, 2022)
Ensuring the security of drinking water supplies, together with fire protection requirements by water supply networks, is a challenge in both legal, operational and research issue. This article presents the essential legal requirements relating to the need of ensuring both the required quality of water delivered to consumers and hydraulic operating parameters of the water pipe network for fire protection purposes. An analysis of threats to the safety of water supply resulting from the bifunctionality of the water pipe network was carried out along with the factors identification of potentially having a negative impact on the drinking water quality. An integral part of the study was the interpretation of the economic and legal consequences for water companies, resulting from the obligation to provide fire protection functions by water supply systems. In addition, the interpretation of risks is presented, both in relation to the health safety of water consumers and to economic consequences, generated by the legal obligation to carry out annual inspections of the hydrant efficiency. The need for further study and analyses of secondary water contamination caused by the fire protection function or its incorrect interpretation has also been demonstrated.
Keywords: water supply system; fire protection; water pipe network; threats; risk; secondary water contamination